Contemporary Issues on Population Poverty and Environmental Crisis in Nepal - Gautam, Dilli Raj (Tribhuvan University Journal, 2010)
Not available. Key words: Population; Poverty and Environmental Crisis; Nepal Tribhuvan University Journal Vol. XIX, 1996 Page: 111-120 Uploaded Date: 24 Nov., 2010